Strategi Promosi dalam Menghadapi Persaingan Global Ditinjau dari Etika Bisnis Islam - Jazuli, Khanif; Fauza, Nilna; Saefullah, Aep; Suharmanto, Suharmanto (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
In response to the increasingly competitive and uncertain business environment, promotional strategies are crucial for companies to sustain and grow. This study aims to analyze the promotional strategies implemented by TPKU Jombang in facing global competition, with a focus on the application of Islamic business ethics. A qualitative descriptive method with a case study approach was employed, involving data collection through interviews, participant observation, and document analysis. The findings reveal that TPKU relies on word-of-mouth promotion as its main strategy, which has proven effective in attracting and retaining customers. However, the company faces challenges in utilizing digital technology to expand its promotional reach, primarily due to limited technological knowledge among its employees. Additionally, the application of Islamic business ethics principles, such as honesty and transparency, plays a crucial role in building consumer trust and maintaining the company's reputation. Therefore, to remain competitive in the global market, TPKU should consider integrating digital technology into its promotional strategies while upholding Islamic ethical principles.